Is the doctrinal identity of Umara al Yamani Ismaili or Shafi‘i ? (Journal of Imam Al-Kadhim College, 2026)
Since every rule has its exceptions, it is necessary to shed light on a poet who has constants that did not change with the change in political circumstances that faced the Fatimid state, unlike the rest of the poets who were subjected to this state with praise or censure, or with both praise and censure, such as Al-Fazari or Sahl Al-Warraq who defeated Ubayy. Yazid Al-Kharji, like most of the jurists of Kairouan, despite the difference in doctrinal structure, believed that the revolution of the owner of the donkey would rid them of the rule of the Fatimids, and here the difference between Amara and his peers - who wander in every valley - becomes clear, like the difference between a pearl and a wasteland, and these constants that Amara remained adherent to made him pay with his life. A tax for her because he did not satirize a country in which he lived for seventeen years, even though poetry was a long-standing weapon in his hands Through it, he can, at the very least, defend the new ruler under the title of piety. However, his poetry was not threatened by his enemies, nor was it used to satirize his opponents, nor did he disavow the insults of yesterday’s companions, and this is one of the important reasons that prompted us to examine the life of this objective poet
Keywords: : intellectuals of Authority, Warraq Plain, sectarianism, Ayyubids; intellectuals of Authority; Warraq Plain; sectarianism; Ayyubids